Test anxiety as a risk factor for use of psychoactive compounds in medical students - Branislava Ćurčić; Dragana Sokolović; Milica Radanović; Dragana Pavlović; Marija Bjeletić; Djordje Vuković; Dragana Drakul (Биомедицинска истраживања, 2024)
Introduction: Test anxiety implies an intense pathological fear in situations of preparing and taking exams which is a significant problem for 15-70% of medical students. The frequent use of psychoactive substances is recognized as a problem for young people. The aim was to determine the frequency and degree of test anxiety and the association with misuse of psychoactive substances in medical students of the Faculty of Medicine in Foča. Methods: The research was conducted according to the principle of a cross-sectional study at the Faculty of Medicine in Foča. Students were offered a custom-made questionnaire containing general and specific questions for test anxiety and use and dependence of psychoactive compounds and social networks. Test anxiety was evaluated by Westside anxiety scale. Results: The sample included 145 respondents, 69.7% females and 30.3% males. The results indicate that the degree of test anxiety does not differ in male and female students, but test anxiety is less pronounced in younger students and students with medium academic success. The level of test anxiety was correlated with the rate of psychoactive compound use. Psychoactive substances were used by 50.3% of students, primary for anti-anxiety, than for psychostimulation and for hypnotic effects. The most commonly used classes of psychoactive substances were plant anxiolytics, followed by benzodiazepines, marijuana, alcohol and narcotics/cocaine (18.6%, 12.4%, 12.4%, 8.3%, and 4.8%, respectively). Conclusion: A significant number of students reach for anxiolytics and other drugs that can create addiction. Elevated levels of test anxiety are positively correlated with increased consumption of psychoactive compounds. However, the frequency of use of psychoactive compounds surpasses the frequency of altogether moderate, high and extreme test anxiety.
Keywords: test anxiety; anxiolytics; psychoactive compounds; plant anxyolitics